DAMPAK PERUBAHAN TARIF PAJAK PENGHASILAN BADAN TERHADAP PERILAKU MANAJEMEN LABA - Oktavia . (Jurnal Akuntansi, 2012)
. This study aims to examine whether companies that earn profits will make earnings management in response to corporate tax rate changes. In addition, this study will also examine whether earnings management is based on tax incentives or non-tax incentives. This study includes 120 samples of profit firms in manufacturing sector between period 2009 â€“ 2010. The result of this study proves that: (1) Profit firms make earnings management in order to respond the corporate tax changes; (2) earnings management performed by profit firms is influenced by tax incentives and non-tax incentives; and (3) non-tax incentive that influenced earnings management is debt.Â Keyword: income tax, corporate tax rate changes, and earnings management.